2007
DOI: 10.3201/eid1311.070705
|View full text |Cite
|
Sign up to set email alerts
|

Protection and Virus Shedding of Falcons Vaccinated against Highly Pathogenic Avian Influenza A Virus (H5N1)

Abstract: Virus shedding by vaccinated birds was markedly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
(36 reference statements)
3
26
1
1
Order By: Relevance
“…Experimental infection of American Kestrels ( Falco sparverius ) by Hall et al (2009) resulted in severe clinical signs (feather fluffing, ataxia, anorexia, tremors, and weight loss) and euthanasia within 4–5 days of inoculation. These findings are consistent with results obtain from the experimental infection of Gyr-Saker hybrid falcons (Lierz et al, 2007). Oropharyngeal swabs from both Kestrels and hybrid falcons reached peak RNA titers one day post-infection and remained positive for the remainder of both studies while cloacal swabs showed a one day delay, peaking at 3–4 days post-infection (Hall et al, 2009; Lierz et al, 2007).…”
Section: H5n1 Influenza In Wild Bird Speciessupporting
confidence: 93%
See 1 more Smart Citation
“…Experimental infection of American Kestrels ( Falco sparverius ) by Hall et al (2009) resulted in severe clinical signs (feather fluffing, ataxia, anorexia, tremors, and weight loss) and euthanasia within 4–5 days of inoculation. These findings are consistent with results obtain from the experimental infection of Gyr-Saker hybrid falcons (Lierz et al, 2007). Oropharyngeal swabs from both Kestrels and hybrid falcons reached peak RNA titers one day post-infection and remained positive for the remainder of both studies while cloacal swabs showed a one day delay, peaking at 3–4 days post-infection (Hall et al, 2009; Lierz et al, 2007).…”
Section: H5n1 Influenza In Wild Bird Speciessupporting
confidence: 93%
“…These findings are consistent with results obtain from the experimental infection of Gyr-Saker hybrid falcons (Lierz et al, 2007). Oropharyngeal swabs from both Kestrels and hybrid falcons reached peak RNA titers one day post-infection and remained positive for the remainder of both studies while cloacal swabs showed a one day delay, peaking at 3–4 days post-infection (Hall et al, 2009; Lierz et al, 2007). Together these studies show raptors are highly susceptible to H5N1 influenza though the natural route of infection and the role of predatory birds in influenza ecology remain unclear.…”
Section: H5n1 Influenza In Wild Bird Speciessupporting
confidence: 93%
“…These differences in the distribution of macroscopic and microscopic lesions might be due to different tissue tropism of the viral strains (Kwon et al, 2011). Vaccination using inactivated H5N1-specific vaccines has been shown to prevent clinical signs of disease following experimental HPAIV H5N1 infection (Lierz et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…H5N1 HPAIVs were also reported to be lethal to other raptor species such as American Kestrel (Falco sparverius) [4], Crested Hawk-eagle (Nisaetus cirrhatus) [22], Eurasian Sparrowhawk (Accipiter nisus) [3], Gyrfalcon-Saker hybrids (Falco rusticolus x Falco cherrug) [1] and Saker Falcon (Falco cherrug) [10]. Gyrfalcon-Saker hybrids can also be infected by feeding on infected prey [1].…”
Section: Discussionmentioning
confidence: 99%